Projeto Educomunicação : formação cidadã na escola de ensino médio Antonio Ferreira Sobrinho, Jaciara (MT) - Carvalho, Elisângela Lopes de Lima (2018)
This research is linked to the research line "Training of Teachers and Public Educational Policies" of the Graduate Program in Education (PPGEdu), UFMT / Rondonópolis. Its theme is "Education and Communication" and as a delimitation the Educommunication Project as a strategy for citizen training and youth protagonism of the Antonio Ferreira Sobrinho High School, Jaciara / MT. The problem that originated this case study started from the following question: Does the Educommunication project contribute as a support for citizen education / emancipation of high school students? Its general objective is to understand how the Educommunication in a High School contributes (or can contribute) to the citizen training of the participating students. To that end, the theoretical reference of this dissertation is based on the proposal of liberating education of Paulo Freire and Célestin Freinet, as well as in the insertion of the media in the school environment, through the educommunication defended by Ismar Soares. This framework is organized in the following axes of analysis: Education and Pedagogy of communication, and serves as support for a dialogic approach on the relation of these axes and the school environment. Thus Freire (1985, 1987, 1995, 2000), Freinet (1977, 1998, 2004) and Soares (1989, 2002, 2011) have theoretical conceptions, which converge on the subject of communication in space school, since these three authors conduct their reflections towards an education focused on the transformation, not only of the student, but of society, including the teacher. Being a case study directed by the dialectical-phenomenological method, it presents methodological concepts based on Freire (1985), Bello (2006), Minayo (2001), Triviños (1987), Bicudo (2011), among others. The data collection took place in three distinct stages: indirect observation, documentary research and semistructured interview, which was directed to 02 teachers and 09 students. The criterion of selection of the interlocutors was the involvement of, at least, two years with the Educommunication Project. The analysis of the data showed that there is a contribution of the project to the citizen training of high school students participating in the project, considering the possibility of expanding this contribution with the offer of specific training on educommunication, not only to the students, but to the other teachers of the project. school. From the research, it was verified that the alterations presented in the Administrative Commissions of the educator in the State of Mato Grosso influenced the results referring to educational activities, pointing out as necessary a reassessment about the hours of availability of this professional, as well as the offer of training aimed at educommunication practice.